Optimal Conditions for Ethanol Production by Simultaneous saccharification and fermentation Using Schizosaccharomyces pombe and Fungal Consortium with Selected Napier Grass Substrate - Sukkaew, Adulsman; Pisapak, Pattama; Kaewmanee, Jutamas; Harinppanwich, Wasantanawin (Science and Engineering Connect, 2025)
Background and Objectives: Ethanol production from lignocellulosic biomass has attracted considerable interest due to the use of renewable resources, reduction of dependence on fossil fuels, and mitigation of environmental impacts. Napier grass (Pennisetum purpureum) is well-suited for ethanol production because of its high cellulose and hemicellulose contents, rapid growth rate, and ease of cultivation. The conversion of lignocellulose into fermentable sugars involving hydrolysis, when combined with fermentation in a single step, can reduce enzyme inhibition caused by sugar accumulation, leading then to enhanced production efficiency. The objective of the present research was therefore to investigate optimal conditions for ethanol production via the Simultaneous saccharification and fermentation (SSF) method using Schizosaccharomyces pombe and fungal consortia, with selected Napier grass as the substrate. Methodology: Completely Randomized Design (CRD) was used to schedule the experiments. Substrate was pretreated with 0.5% sulfuric acid at 140 °C for 60 minutes, followed by microwave treatment at 700 W for 15 minutes. Cellulase enzyme was then added at a concentration of 20 U; incubation was then conducted for 48 hours. Subsequently, the mixture was subject to Simultaneous saccharification and fermentation (SSF) using Schizosaccharomyces pombe in combination with fungal strains from the genera Trichoderma, Aspergillus, Rhizopus, and Penicillium. Eight different fermentation formulations were tested. Main Results: Fermentation of Napier grass via the Simultaneous saccharification and fermentation (SSF) process using S. pombe at a concentration of 10% in combination with Trichoderma sp. at a concentration of 5% for 102 hours yielded a maximum ethanol production of 69.91 g/L. The total soluble solids content remained at 5.10 °Brix, while the residual reducing sugar content was 45.23 mg/g dry weight. After the fourth distillation, the ethanol concentration reached 88.29% v/v. Conclusions: Co-cultivation of the yeast Schizosaccharomyces pombe and the fungus Trichoderma sp. under optimized fermentation conditions significantly enhanced the efficiency of ethanol production from Napier grass. A continuous decrease in reducing sugars and total soluble solids was observed during fermentation, corresponding to the increase in ethanol concentration. Practical Application: The findings of the present study can be applied to the development of ethanol production technologies from biomass materials at scales ranging from small to large industrial operations. In regions where Napier grass is locally cultivated as an energy crop, the approach offers a potential to produce renewable energy, reduce dependence on fossil fuels, and add value to community bioresources. Furthermore, it provides a strategic framework for the sustainable management of biomass resources.